1990
DOI: 10.1093/oxfordjournals.aje.a115491
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Human Immunodeficiency Virus Type 1 (Hiv-1) Infection in Patients at a Sexually Transmitted Disease Clinic in New York City

Abstract: Patients who attended a sexually transmitted disease clinic in New York City in 1987 were offered enrollment in a nonblinded study to estimate human immunodeficiency virus type 1 (HIV-1) seroprevalence in adults with multiple sexual partners and to determine risk factors associated with HIV-1 infection. In addition, a blinded serosurvey of a representative sample of patients was performed to obtain an unbiased estimate of seroprevalence in clinic attendees. The seroprevalence in the blinded serosurvey was 7.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Substantial research has found that drug-involved men are at disproportionately high risk of engaging in transmission risk behaviors for HIV and other sexually transmitted infections (STIs) [1][2][3][4] as well as of perpetrating intimate partner violence (IPV) against women. [5][6][7][8][9][10][11][12][13][14] Over the past decade, mounting evidence also has documented multifaceted relationships between experiencing IPV and HIV/STI transmission risks among drug-involved women.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial research has found that drug-involved men are at disproportionately high risk of engaging in transmission risk behaviors for HIV and other sexually transmitted infections (STIs) [1][2][3][4] as well as of perpetrating intimate partner violence (IPV) against women. [5][6][7][8][9][10][11][12][13][14] Over the past decade, mounting evidence also has documented multifaceted relationships between experiencing IPV and HIV/STI transmission risks among drug-involved women.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has documented associations between drug and alcohol use and perpetration of IPV among men (Berenson et al, 1991;El-Bassel et al, 2001;Miller, 1995). Numerous studies have also linked drug and alcohol use with having unprotected sex, sex with a risky partner, sex with multiple partners, exchanging sex for money or drugs, as well as with HIV and other STDs (Chiasson et al, 1990;Edlin et al, 1992Edlin et al, , 1994El-Bassel et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the definition of bisexuality used and the population studied, previous estimates of bisexuality among men who report having sex with men have ranged from 13 percent to 85 percent (6)(7)(8)(9). Estimates of HIV seroprevalence in bisexual men have ranged Lehner and Chiasson from 13 percent in a low seroprevalence area (6) to 35 percent in New York City (7).…”
Section: Discussionmentioning
confidence: 99%